PENGARUH MEDIA VIDEO INTERAKTIF BERBASIS KINEMASTER TERHADAP HASIL BELAJAR PADA SISWA KELAS 3 MATA PELAJARAN IPAS - Clarisa Putri Arlinda; Wahyu Susiloningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this research is to analyse the impact of using interactive videos on students' scores in the IPAS subject for Year III at SDN Menanggal 601 Surabaya. The low level of students' understanding of IPAS material, particularly regarding energy in our surroundings, serves as the background of this study. During the learning process, many students tend to be more interested in talking or playing on their own, which negatively affects their academic performance, as evidenced by persistently low scores. This study adopts a quantitative approach using a quasi-experimental design. The model employed is the nonequivalent control group design. The research was conducted at SDN Menanggal 601 Surabaya with a sample size of 60 students, selected through random sampling. Data collection was carried out using achievement tests, and data analysis involved prerequisite tests, including normality and homogeneity tests. To test the hypothesis, a t-test was conducted to explore the impact of interactive videos on students' learning outcomes in Year III IPAS lessons. The study results revealed that the average post-test score in the experimental group reached 78.67, while the control group only achieved a significantly lower average of 57.00. According to hypothesis testing using an independent sample t-test, the significance level (2-tailed) was found to be 0.001.